Extraskeletal mesenchymal chondrosarcoma of the abdomen: A rare clinical presentation (Indian Journal of Case Reports, 2024)
Extraskeletal mesenchymal chondrosarcoma (EMCS) is a rare malignant soft tissue tumor of chondroprogenitor cell origin. Originally, it was restricted to the bone only but that is no longer the case. Recent literature reports that 20–33% of these tumors occur at the extraskeletal sites. We report one such case, in which the tumor involved the anterior abdominal wall muscles and also had a large intra- abdominal mass that covered a large part of the peritoneal cavity. The clinical features and computed tomography findings suggested the diagnosis of a malignant desmoid tumor with intra-abdominal extension; however, the histopathological examination and the immunohistochemistry proved the tumor to be EMCS. The case is reported due to the dilemma in diagnosis, its rarity, large size, parietal, and intra-abdominal extension with multiple site involvement.